Enhanced Saccharification and Fermentation of Rice Straw by Reducing the Concentration of Phenolic Compounds Using an Immobilized Enzyme Cocktail. Issue 6 (8th May 2019) - Kumar, Virendra; Patel, Sanjay K. S.; Gupta, Rahul K.; Otari, Sachin V.; Gao, Hui; Lee, Jung‐Kul; Zhang, Liaoyuan
Abstract : The production of bioethanol from rice straw can contribute to the rural economy and provide clean fuel in a sustainable manner. However, phenolic compounds, which are mostly produced during acid pretreatment of biomass, act as inhibitors of fermenting microorganisms. Laccase is well known for its ability to oxidize lignin and phenolic compounds derived from lignocellulosic biomass. In the present study, an immobilized enzyme cocktail containing laccase was isevaluated in regard to its ability to enhance the saccharification and fermentation processes by reducing the amount of phenolic compounds produced. Saccharification of rice straw with the laccase‐supplemented immobilized enzyme cocktail reduced phenolic compounds by 73.8%, resulting in a saccharification yield of 84.6%. In addition, improved yeast performance was is noted during the fermentation process, resulting in a 78.3% conversion of sugar into ethanol with an ethanol productivity of 0.478 g/L/h. To the best of our knowledge, this is the first description of the use of an immobilized enzyme cocktail comprised of Celluclast 1.5L, β‐glucosidase, and laccase for the production of bioethanol from rice straw. This study details a potential approach to producing biofuels from agricultural biomass, the applicability of which can be improved through up‐scaling. Abstract : A cocktail of immobilized enzymes composed of celluclast 1.5L, ß‐glucosidase, and laccase is used to carry out degradation of phenolic compounds and saccharification of pretreated rice straw simultaneously. The repeated use of immobilized enzymes offers advantages compared to free enzyme cocktails. This strategy also leads to the improved fermentation efficiency of yeast and enhanced ethanol production using rice straw. A cocktail of immobilized enzymes composed of celluclast 1.5L, ß‐glucosidase, and laccase is used to carry out degradation of phenolic compounds and saccharification of pretreated rice straw simultaneously. The repeated use of immobilized enzymes offers advantages compared to free enzyme cocktails. This strategy also leads to the improved fermentation efficiency of yeast and enhanced ethanol production using rice straw. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org.